Translational activity of the splicing factor SRSF1 is required for development and cilia function - Haward, Fiona; Maslon, Magdalena; Yeyati, Patricia; Bellora, Nicolás; Hansen, Jan; Aitken, Stuart; Lawson, Jennifer; von Kriegsheim, Alex; Wachten, Dagmar; Mill, Pleasantine; Adams, Ian; Caceres, Javier (Cold Spring Harbor Labs Press, 2020)
Fil: Haward, Fiona. University of Edinburgh; Reino Unido